O papel da presidência na gest\~ao da coordenaç\~ao política governamental: Arranjos e dinâmicas de poder com a coaliz\~ao (1995-2010) - Camila Romero Lameir\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The analysis of the relations between the Executive and Legislative Federal, in Brazil, relate the support of the partisan coalition to government initiatives in Congress with the parties'representation of the base in the ministries. These approaches suppose an understanding that the distribution of cabinet's role in Executive branch fulfills the function of coordinating the actions of partisan coalition to government interests. It is intended in this study precisely qualify this coordination. How, in the exercise of their terms, presidents mobilize and organize their government to interact with the legislature and their partisan coalition? This is the starting point of this work. Under an analytical perspective that emphasizes organizational structure and attributions of the Presidency, precisely at the Civil House, the text discusses how, particularly, Fernando Henrique Cardoso and Luiz Inácio Lula da Silva managed the political coordination of their government. Under an institutional approach, introduced in the field of presidential studies by Terry Moe, the work intends to analyze the president's levels of control on political coordination structures project in the Presidency. It is argued that in some periods, to galvanize the support of their coalition, the presidents not only expand the representation of their partisan base in cabinet's role in Executive branch, but grant spaces in their own power structure, the Presidency, to the members of the coalition. Based on specific variables, will be to see that there are several political articulation arrangements arranged along their respective terms and they express different levels of control of the president.
Keywords: D73; E61; 330; Civil House; appointments; political appointments; patronage; Presidency; political coordination; state capacity; cash transfer programs; social policies; Brazil; Argentina; South Africa